Protein precoating modulates biomolecular coronas and nanocapsule–immune cell interactions in human blood. Issue 37 (17th June 2022) - Li, Shiyao; Ju, Yi; Zhou, Jiajing; Faria, Matthew; Ang, Ching-Seng; Mitchell, Andrew J.; Zhong, Qi-Zhi; Zheng, Tian; Kent, Stephen J.; Caruso, Frank
Abstract : We demonstrate the effects of protein precoating on biomolecular corona formation and immune cell interactions of metal–phenolic network nanocapsules using proteomics analyses and human blood assays. Abstract : The biomolecular corona that forms on particles upon contact with blood plays a key role in the fate and utility of nanomedicines. Recent studies have shown that precoating nanoparticles with serum proteins can improve the biocompatibility and stealth properties of nanoparticles. However, it is not fully clear how precoating influences biomolecular corona formation and downstream biological responses. Herein, we systematically examine three precoating strategies by coating bovine serum albumin (single protein), fetal bovine serum (FBS, mixed proteins without immunoglobulins), or bovine serum (mixed proteins) on three nanoparticle systems, namely supramolecular template nanoparticles, metal–phenolic network (MPN)-coated template (core–shell) nanoparticles, and MPN nanocapsules (obtained after template removal). The effect of protein precoating on biomolecular corona compositions and particle–immune cell interactions in human blood was characterized. In the absence of a pre-coating, the MPN nanocapsules displayed lower leukocyte association, which correlated to the lower amount (by 2–3 fold) of adsorbed proteins and substantially fewer immunoglobulins (more than 100 times) in the biomolecular corona relative to the template and core–shell nanoparticles. Among the three coating strategies, FBS precoating demonstrated the most significant reduction in leukocyte association (up to 97% of all three nanoparticles). A correlation analysis highlights that immunoglobulins and apolipoproteins may regulate leukocyte recognition. This study demonstrates the impact of different precoating strategies on nanoparticle–immune cell association and the role of immunoglobulins in bio–nano interactions.